EVALUASI KUALITAS BEBERAPA JENIS MINYAK GORENG KEMASAN SETELAH DIPANASKAN MENGGUNAKAN SIFAT ELEKTROOPTIS - Murni, Sri; Bawono Putranto, Ari; Hidayanto, Eko; Firdausi, K Sofjan (BERKALA FISIKA, 2013)
In this report, we have determined the average value of polarization angle for various edible oils, before and after heating. The change of polarization angle was measured averagebetween potential differences 0-9 kV. The heating time for the samples was conducted up to 10 hours at average temperature by 180°C. The source of light was He-Ne Laser 1 mW (633 nm) with optical length of samples of 1 cm. In agreement to the previous experiment, our result shows that all vegetable oils provide increasing of free radicals indicated by increasing polarizationangle for longer heating time. For the heating time interval 0-10 hours, the level degradation ofoil rises quadratically. From various edible oils, olive oil is still the relative best quality from allsamples in this experiment. This method, once again, shows more powerful relative to otherstandard methods.Keywords: frying oil, electrooptics, polarization angle